KARAKTERISTIK MEKANIS BETON YANG MENGGUNAKAN IRON SLAG SEBAGAI AGREGAT HALUS - -, Hijriah; Yunianti, Nur Hadijah (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2020)
The demand for environmentally friendly concrete mixtures is currently increasing due to an increase in global temperatures. Therefore, innovation is needed in the world of Civil Engineering to produce structures that can reduce global warming. One alternative that can be taken is by utilizing materials from environmentally friendly products such as Iron Slag. This study aims to determine the characteristics of the aggregate and to analyze the strength of the concrete mixture using Iron Slag as a substitute for fine aggregate. This research is an experimental study which was conducted in the Laboratory of Concrete and Structural Materials, Bosowa University. Variations in the test object were the levels of addition of Iron Slag with levels of 0%, 25% and 50%. The test object will be observed at the age of 28 days, where the number of test objects is 29 pieces. The tests carried out include testing the characteristics of the materials used, both coarse and fine aggregates, as well as testing the compressive strength of the concrete. Based on the results of the research analysis, it was concluded that Iron Slag waste met the criteria as fine aggregate for concrete mixtures.